1981
DOI: 10.1099/00221287-127-1-35
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Sporulation Medium and Germination Ability of Mucor racemosus Sporangiospores

Abstract: Asexual sporangiospores of Mucor racemosus produced on a minimal sporulation medium (M spores) germinated only if glucose, mannose or a complex substrate such as peptone, yeast extract or Casamino acids was present. Once germinated, growth was supported by a wide range of substrates including amino acids, carbohydrates or organic acids. Sporangiospores produced on a nutritionally complex sporulation medium (C-spores) germinated on a wide range of carbon sources. C-spore phenotype was pleiotropic in that sporan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…As previously reported (Tripp & Paznokas, 1981), greater than 95% of M-and C-spores of M . racernosus germinate in MGM containing glucose, peptone or Casamino acids; but no M-spores and only a portion of C-spores germinate in the presence of glutamate or alanine.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…As previously reported (Tripp & Paznokas, 1981), greater than 95% of M-and C-spores of M . racernosus germinate in MGM containing glucose, peptone or Casamino acids; but no M-spores and only a portion of C-spores germinate in the presence of glutamate or alanine.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, the addition of exogenous cyclic AMP stimulated the rate of 3-OMDG-triggered protein loss in C-spores but did not initiate it (Fig. 6), and may explain why the rate of swelling but not the percentage of a C-spore population germinating on glutamate was stimulated by cyclic AMP (Wertman & Paznokas, 1981;Tripp & Paznokas, 1981). The observation that cyclic AMP stimulates the rate of protein degradation is not unique to M .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Effects of glucose analogues on germination Previous studies (Tripp & Paznokas, 1981) have shown that Mucor racernosus sporangiospores are initiated to germinate synchronously and completely by glucose or the glucose analogue 3-0-methyl-~-glucose. Both C-and M-spores were treated with a number of compounds that are structurally related to glucose (Table 1) in a medium which also contained yeast nitrogen base, ammonium sulphate and glutamate.…”
Section: R E S U L T Smentioning
confidence: 99%
“…Sporangiospore volume was monitored with a Coulter counter (model ZB 1) and Channelyzer (model 11) as previously described (Tripp & Paznokas, 1981). Greater than 90% of either M-spores or C-spores have a volume (45 pm3 at the time of harvesting.…”
Section: L T R I P P a N D J L P A Z N O K A Smentioning
confidence: 99%